Student Group Dynamic Model Based on Understanding in Mathematics Subjects - M. Ivan Ariful Fathoni; Anisa Fitri; Hanifahtul Husnah (Mathematics Department, Faculty of Science and Technology, UIN Sunan Ampel Surabaya, 2021)
This study discusses the interaction of students with a mathematical modeling point of view. This interaction involves students who understand and do not understand mathematics subject matter. The interaction process between groups is modeled in a two-dimensional system of differential equations. Variable A is the percentage of students who understand the material, and variable B is the percentage of students who do not understand the material. The dynamic analysis results obtained by one trivial equilibrium point and three non-trivial equilibrium points exist with several conditions. Based on the stability analysis of the non-trivial equilibrium point, it is found that the conditions without students do not understand mathematics subject matter. This condition is the goal of this study, which involves interaction between students; it can increase the learning process's success.